2020
DOI: 10.1038/s41598-020-68974-4
|View full text |Cite
|
Sign up to set email alerts
|

Glycolaldehyde-modified proteins cause adverse functional and structural aortic remodeling leading to cardiac pressure overload

Abstract: Growing evidence supports the role of advanced glycation end products (AGEs) in the development of diabetic vascular complications and cardiovascular diseases (CVDs). We have shown that high-molecular-weight AGEs (HMW-AGEs), present in our Western diet, impair cardiac function. Whether HMW-AGEs affect vascular function remains unknown. In this study, we aimed to investigate the impact of chronic HMW-AGEs exposure on vascular function and structure. Adult male Sprague Dawley rats were daily injected with HMW-AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, the accumulation of superoxide has been shown to be the cause of the attenuated endothelium-related relaxation capacity in diabetic rat aortae [ 44 ]. Furthermore, our group demonstrated previously that impaired endothelium-dependent relaxation caused by sustained increased levels of HMW-AGEs is mediated by an increased superoxide formation [ 25 ]. In the current study, we show that SOD improves the endothelium-dependent relaxation in aortic rings that are acutely preincubated with HMW-AGEs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the accumulation of superoxide has been shown to be the cause of the attenuated endothelium-related relaxation capacity in diabetic rat aortae [ 44 ]. Furthermore, our group demonstrated previously that impaired endothelium-dependent relaxation caused by sustained increased levels of HMW-AGEs is mediated by an increased superoxide formation [ 25 ]. In the current study, we show that SOD improves the endothelium-dependent relaxation in aortic rings that are acutely preincubated with HMW-AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the vascular NO content also relies on the activity of the NO-producing enzyme eNOS [ 50 ]. The recent work of our group showed that the impaired aortic relaxation observed after chronic HMW-AGE exposure is not due to reduced eNOS activity [ 25 ]. In that context, the underlying mechanisms of AGEs for vascular dysfunction can differ between acute and chronic circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive hemodynamic measurements were obtained at sacrifice under 2% isoflurane anesthesia supplemented with oxygen, as described before [57]. Hemodynamic parameters were measured with an SPR-320 Mikro-Tip single pressure catheter (Millar Inc., The Hague, The Netherlands) placed into the LV via the right carotid artery.…”
Section: Hemodynamic Measurementsmentioning
confidence: 99%
“…Additionally, in cardiovascular diseases [27], Alzheimer's disease, and cancer, AGEs have been proven to display a causative role [28]. They can accumulate throughout the body in various tissues such as in the heart [29], blood vessels [30], lungs [31], and adipose tissue [32], exerting long-term effects.…”
Section: Introductionmentioning
confidence: 99%